Hubungan Kebiasaan Belajar Dengan Nilai Biologi Siswa Kelas VIII MTsN Durian Tarung Padang Tahun Pelajaran 2012/2013 - Putri, Ayumi Meiriza; Ardi, Ardi; Nerita, Siska (STKIP PGRI Sumbar, 2013)
ABSTRAKÂ Education canât be separated with studying because studying is mainly basic of education. Studentsâ learning results are shown from testing such as quizzes and examination. This research aimed to determine the correlation between studentsâ learning habit and studentsâ learning result in Biology lesson class VIII MTsN Durian Tarung Padang year 2012/2013. This was descriptive research. The result showed that tcount was 2.44 and ttable was 1.68. It meant to count > table. So, there was positive a significant correlation between studentsâ learning habit and studentsâ learning result in Biology lesson class VIII MTsN Durian Tarung Padang year 2012/2013. Therefore it can be concluded, the better learning habits can make the higher biological value of eighth grade students MTsN Tarung Padang Durian Academic Year 2012/2013.Â